Upravlenie trenirovochnym protsessom begunov na korotkie distantsii na osnove ucheta individual'nykh osobennosti - Chernysheva, E. N. (Teorija i Praktika fiziceskoj Kul'tury, 2000)
Article describes how the training process of short distance runners can be managed on the basis of taking into account their individual pecularities.